Representation of the ‘Other’ in Malaysian Film: Kadazandusun Identity in Sabah Indigenous Telemovie - Sydney Thomas, Sibangan; Miaw Lee, Teo; Candida, Jau Emang (2021)
As a nation of multicultural society, Malaysia consists of various ethnic group with different backgrounds. From a national context, the need for racial integration into a singular national identity is crucial to structure unity among the people in Malaysia. With strict supervision from the local government, film in Malaysia plays a significant role to incorporate the diverse society by portraying the accepted Malaysia national identity. However, the concept of national identity is based on an ‘imagined’ assumption, as the Malaysia national cinema are largely dominated and exclusively representing the Malay majority. This resulted in the lack of representation toward ‘other’ ethnics in the film especially the indigenous of Sabah. By referring to Benedict Anderson’s theoretical framework of “imagined communities”, this paper attempts to situate Sabah indigenous film within the context of Malaysia national cinema and argue the distinction of self-identification possess by the Sabah indigenous. This is accomplished through analysing two Kadazandusun telemovies produced by Alfred Ujin. The paper concludes the indigenous ethnic in Sabah identified themselves separately from the national identity. The indigenous filmmaker utilised film to expressed their identity through the depiction of indigenous language, culture and value. Keywords: Sabah filmmaking, Indigenous filmmaking, Kadazandusun identity, telemovie, film studies.